Surface instabilities in a Mooney–Rivlin body with frictional boundary conditions - Désoyer, T.; Martins, J.A.C. (International journal of adhesion and adhesives, 1998)
The dynamic stability of the steady frictional sliding of a Mooney–Rivlin half-space compressed against a rigid flat surface is studied. The linearized system of differential equations that governs the small plane oscillations of the elastic body about an homogeneous steady-sliding deformation state is established. It is shown that, for sufficiently large coefficients of friction and shear strains, surface flutter or divergence instabilities may occur. Some features of the corresponding linearized dynamic solutions are qualitatively discussed by comparison with some experimental observations.